Otra broma de Elmer - McKee, David (Mexico, D.F. : Fondo de Cultura Economica, 1994)
Elmer, the patchwork elephant, plays an amusing trick on his grey elephant friends.
Translation of: Elmer again.
Keywords: Elephants -- Fiction; Practical jokes -- Fiction; Spanish language materials -- Fiction; Picture books; Fiction